Analysis of conditions of the quartz surface photochemical polishing by way of profile optimization. Issue 2 (13th July 2020) - Kanevskii, Vasyl; Kolienov, Serhii
Abstract : Purpose: The purpose of this paper is to show the possibility of using the quartz regular surface profile in the form of protrusions and troughs of a triangular shape instead of a random surface profile characterized by a Gaussian correlation function when analyzing the electromagnetic field parameters above the quartz surface to determine the conditions of the effective surface subnano-polishing. Design/methodology/approach: The numerical determination of the evanescent field optimal configuration formed near the quartz rough surface coated with an aqueous solution of calcium hypochlorite when illuminated from the side of the solution has been considered. The finite-element approach is used to solve the Helmholtz two-dimensional vector equation. Findings: Conditions of effective photochemical polishing of rough surface with profile in the form of triangular protrusions and troughs to a sub-nanometer level of roughness are found. These optimal conditions are achieved when the light falls normally on the quartz surface and the height of the surface protrusions is small (up to 20 nm). Originality/value: This paper shows the possibility of simplifying electrodynamic calculations and analyzing an evanescent field near a quartz surface for the purpose of photochemical polishing by replacing the random profile function with a deterministic periodic function. That is, the novelty of this paper, which supplements the works published earlier [ Journal of Modern Optics, 67 (3) (2020):242–251; Optik, 207 (2020):164438].